2019
DOI: 10.1186/s13059-019-1778-0
|View full text |Cite
|
Sign up to set email alerts
|

TOAST: improving reference-free cell composition estimation by cross-cell type differential analysis

Abstract: In the analysis of high-throughput data from complex samples, cell composition is an important factor that needs to be accounted for. Except for a limited number of tissues with known pure cell type profiles, a majority of genomics and epigenetics data relies on the "reference-free deconvolution" methods to estimate cell composition. We develop a novel computational method to improve reference-free deconvolution, which iteratively searches for cell type-specific features and performs composition estimation. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 73 publications
(136 reference statements)
1
56
0
Order By: Relevance
“…Such reference datasets are much more widely available than compartment-specific expression on the same targeted panel. We benchmarked DeCompress against reference-free methods (20,22,(24)(25)(26) using in-silico GTEx mixing experiments (53,54), 4 published datasets with known compartment proportions (11,23,58,59), and a large, heterogeneous NanoString nCounter dataset from the CBCS (43,55). In these analyses, we showed that DeCompress recapitulated true compartment proportions with the minimum error and the strongest compartment-specific positive correlations, especially when the reference dataset is properly aligned with the tissue assayed in the target.…”
Section: Unlike Traditional Reference-based Methods That Require Compmentioning
confidence: 99%
See 2 more Smart Citations
“…Such reference datasets are much more widely available than compartment-specific expression on the same targeted panel. We benchmarked DeCompress against reference-free methods (20,22,(24)(25)(26) using in-silico GTEx mixing experiments (53,54), 4 published datasets with known compartment proportions (11,23,58,59), and a large, heterogeneous NanoString nCounter dataset from the CBCS (43,55). In these analyses, we showed that DeCompress recapitulated true compartment proportions with the minimum error and the strongest compartment-specific positive correlations, especially when the reference dataset is properly aligned with the tissue assayed in the target.…”
Section: Unlike Traditional Reference-based Methods That Require Compmentioning
confidence: 99%
“…First, DeCompress has a high computational cost, owing mainly to its lengthy compressed sensing training step. We recommend running mainly linear optimization methods in this step and have implemented parallelization options to bring computation time on par with the iterative framework proposed in TOAST (25). However, DeCompress estimates compartment proportions both accurately and precisely, compared to other reference-free methods, and provides a strong computational alternative that is much faster than costly lab-based measurement of composition.…”
Section: Unlike Traditional Reference-based Methods That Require Compmentioning
confidence: 99%
See 1 more Smart Citation
“…Root mean square error (RMSE) directly measures the error between the actual and predicted values for a cell type. A detailed discussion of these metrics and other alternatives are presented by Li and Wu [20].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, various computational approaches had been developed to investigate the purities of tumor biopsies. These methods had successfully utilized the molecular signatures, such as gene expressions (e.g., the ESTIMATE algorithm [2] ), copy number aberrations (e.g., the ABSOLUTE algorithm [3] ) and DNA methylations (e.g., the LUMP algorithm [1] ), to either estimate the purity [4] , [5] , [6] , [7] , or decode the cell compositions of biopsy samples [8] , [9] , [10] , [11] , [12] , [13] , [14] . Despite the high accuracy and consistency demonstrated in these studies, however, the majority of these methods only focused on biopsy samples from the TCGA (The Cancer Genome Atlas) project [15] and very few had been validated outside the TCGA datasets.…”
Section: Introductionmentioning
confidence: 99%